Proceedings of the 25th International Conference on Intelligent User Interfaces 2020
DOI: 10.1145/3377325.3377497
|View full text |Cite
|
Sign up to set email alerts
|

Detecting errors in pick and place procedures

Abstract: Many human activities, such as manufacturing and assembly, are sequence-constrained procedural tasks (SPTs): they consist of a series of steps that must be executed in a specific spatial/temporal order. However, these tasks can be error prone -steps can be missed out, executed out-of-order, and repeated. The ability to automatically predict if a person is about to commit an error could greatly help in these cases. The prediction could be used, for example, to provide feedback to prevent mistakes or mitigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Future work can extend to additionally include eye gaze in modeling human states, which prior works have suggested to be indicative of robot states (e.g., errors) during situated interactions. Research has shown how gaze cues may be used to understand human intent (e.g., [14]) and robot actions (e.g., [26]), as well as how they can be utilized to enhance robot learning from human demonstration [25], detect errors [2,3], and facilitate efficient human-robot collaboration [15]. All in all, multimodal human signals present opportunities to enhance human-robot interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work can extend to additionally include eye gaze in modeling human states, which prior works have suggested to be indicative of robot states (e.g., errors) during situated interactions. Research has shown how gaze cues may be used to understand human intent (e.g., [14]) and robot actions (e.g., [26]), as well as how they can be utilized to enhance robot learning from human demonstration [25], detect errors [2,3], and facilitate efficient human-robot collaboration [15]. All in all, multimodal human signals present opportunities to enhance human-robot interaction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, people respond differently when facing social norm violations and technical failures; in particular, technical failures generally resulted in fewer social signals and faster reaction times [20]. Prior works have demonstrated how social signals such as upper body movements (e.g., [28]), gaze (e.g., [2,3]), and gestures (e.g., [3]) can be used to detect errors effectively. It is worth noting that most of these prior works used human-like robots, which have been shown to elicit different responses to failures than non-humanoid embodiments in social error scenarios [17].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Another feature of manual assembly tasks in manufacturing is that they can be considered sequenceconstrained procedural tasks (SPTs). According to Bovo et al [59], an SPT comprises a set of steps that must be performed in a specific temporal order. Following SPTs by workers can be associated with several errors: steps can be carried out in the wrong order, they can be omitted, or they can be repeated, among others.…”
Section: Resultsmentioning
confidence: 99%
“…The application of the Intelligent Poka-Yuke technology achieves a number of benefits, the most important of which are (Bovo, et al, 2020, 540) [3] : 1. Information inspection: In order to support and improve production processes, it is carried out using ~ 103 ~ smart sensors and computer vision systems, to detect all errors and defects (data and information), analyze them in a timely manner, and use them to discover possibilities for error prevention and improvement.…”
Section: Benefits Of Intelligent Poka-yukementioning
confidence: 99%